Efeito do antipsicótico haloperidol em Caenorhabditis elegans e do extrato bruto de Piper methysticum em camundongos sobre parâmetros comportamentais e bioquímicos - Krum, Bárbara Nunes (2021)
Psychotic disorders, as schizophrenia and substance-induced psychoses (amphetamine, for example), are characterized by the appearance of delusions, hallucinations and other, and their symptoms are associated with hyperactivation of the mesolimbic dopaminergic pathway. Antipsychotics antagonize D2-type dopamine (DA) receptors in this pathway and due to it, they have been used for the treatment of psychotic symptoms. Herbal medicines have also been used as alternatives to the treatment of symptoms of central nervous system (CNS) disorders. Piper methysticum (P. methysticum), named Kava Kava, fits in this context because it has action on GABAergic and dopaminergic receptors, on the enzyme monoamine oxidase (MAO) and others. Research in animal models, such as in Caenorhabditis elegans (C. elegans) and rodents, has been carried out to better understand the symptoms, pharmacological treatment and its mechanisms, as well as the use of possible adjuvants to the pharmacological therapy of psychotic disorders. Thus, the first main of this study was to investigate the effects of the antipsychotic haloperidol on the dopaminergic system in C. elegans. The animals were exposed to haloperidol (80 or 160 μM) for 1-6 days and behavioral, molecular and morphological assays were performed. Haloperidol increased survival, decreased locomotor behavior and DA levels in these animals, but it did not alter neither dop-1, dop-2 and dop-3 genes expression, nor the morphology of cephalic dopaminergic neurons. Moreover, locomotion speed recovered to basal conditions upon haloperidol withdrawal. Haloperidol’s effects on C. elegans seem to be related to modulation of the D2-type DA receptor. Regarding the herbal medicine Kava Kava, the crude extract was used to investigate its effects in an animal model of psychosis-like symptoms induced by amphetamine on behavioral changes and on MAO activity. Mice received Kava extract (40 mg/Kg) or vehicle (corn oil) by gavage; 2 h later, amphetamine (1.25 mg/kg) or vehicle (0.9% NaCl) by an intraperitoneal injection. 25 min later, behavioral tests showed that Kava extract exhibited anxiolytic effect in the elevated plus-maze test, increased the locomotor activity in the open-field test and decreased MAO-A activity in the cortex and MAO-B activity in the hippocampus of the animals. Kava extract prevented the effects of amphetamine on stereotyped behavior and, the co-treatment increased the number of entries into arms in Y maze test as well as MAO-B activity in striatum of mice. However, the hyperlocomotion induced by amphetamine was not altered by previous treatment with the extract. The social interaction was not modified for the treatment. The results showed that Kava extract avoided the increase of stereotyped behavior induced by amphetamine in mice, which could be investigated as a possible adjuvant in the pharmacological therapy to minimize psychotic symptoms in patients. Lastly, the third main of this study investigated the effect of Kava extract (10-400 mg/kg, by gavage) on MAO activity in different mouse brain structures and on behavioral changes after 21 days of treatment as well as, in in vitro assays (10-100 μg/ml of the extract) in mouse brain homogenate. Kava extract increased the percentage of entries into the open arms in the plus-maze test and decreased MAO-B activity in the cortex (10 mg/kg) and in the region containing the substantia nigra (10 and 100 mg/kg) in assays ex vivo. In vitro, Kava extract reversibly inhibited MAO-B activity with IC50 of 14.62 μg/mL, increased Km values (10, 30 μg/ml) and decreased Vmax (100 μg/ml). Thus, the extract showed different effects on MAO-B isoform depending on the brain structure evaluated, which could be promissory in pathologies where MAO-B is the pharmacological target. The totality of results presented in this thesis revealed useful results conditioned to psychosis, information which becomes relevant for future studies related to this disorder.